Compliance to cardiovascular treatment: clinicians and patients’ problem - G. V. Pogosova; I. E. Koltunov; G. Yu. Melik-Ogandzhanyan; O. Yu. Sokolova (Кардиоваскулярная терапия и профилактика)
This literature review discusses various aspects of therapy compliance in cardiovascular patients. The clinician and patient-related causes of low compliance are analysed, and potential effectiveness of complex educational approach is emphasised. The results of major national and international studies (e.g., RELIPH Study) are presented.